Teatr duszy Władysława St. Reymonta. O antynomiach postaw epistolarnych noblisty - Osińska, Anna (Colloquia Litteraria, 2020)
The preserved letters of Wladyslaw Stanislaw Reymont reveal a broad spectrum of the sender’s epistolary attitudes, related not only to the artistic activity of the Nobel Prize winner, but also to his social functions. The article demonstrates the correspondence of Reymont in terms of showing antinomic attitudes and the diversity that shapes them. The author focuses on the ways of constructing postal statements and the possibilities they create in the interpretation.